DAMPAK PERUBAHAN KARAKTERISTIK USAHA TERHADAP KEPUTUSAN EKONOMI RUMAHTANGGA PENGRAJIN ROTAN - Nugrahadi, Eko Wahyu (Universitas Muhammdaiyah Surakarta, 2005)
Actually, rattan handicraft home industry can play three roles in the same time, as a worker supplier, producer, and consumer. In this way, we can see the relation of working time allocation, income, and household spending pattern as a system (household economic decision). In doing its economic decision, a household always interacts with its environment. Any environmental changes outside the household, such as material costs, output price, business scale, and business pattern (business characteristic factor) will give direct or indirect influence.This writing is based on the result of a research done in Sei Sikambing rattan handicraft industrial village, Medan Petisah District, Medan. The population of the research was rattan craftsman household. The sample was taken from the population using simple random sampling technique that is 35 rattan home craftsmen. The primary and secondary data gathered were analyzed based on the econometric model with 2SLS method. The analysis is conducted by performing a simulation entails several scenario alternatives.Based on the analysis result, it is found that: (I) improving business scale to small industry and changing the business pattern to subcontract may rise income and outcome for consumption and investment, (2) if these changes are done along with any rise of material and rattan products price, the income and outcome for consumption and investment will be higher, and (3) those changes will give effects to the development of job opportunity in rattan industry, unless there are any changes on the business pattern.